Ocular air gun injuries: a one-year surveillance study in the UK and Eire (BOSU). 2001–2002 - Shuttleworth, G N; Galloway, P; Sparrow, J M; Lane, C (Eye (London), 2009)
Aims The vulnerability of the eye means that ocular air gun injuries figure prominently in the medical literature. This Study reports the results of the first ocular air gun injury surveillance study. Methods Ocular air gun injuries were reported to the British Ophthalmic Surveillance Unit (BOSU; United Kingdom and Eire) for the period November 2001–December 2002 (13 months). Two questionnaires were used to collect demographic details, circumstances of injury, details of injuries, medical management and outcome. Results A total of 105 initial and 99 follow-up questionnaires were returned. Eighty-six ocular air gun injuries occurred during the last 12 months of surveillance yielding a corrected, estimated incidence of 91–115 injuries/year. Injuries were most frequent in August/September, and 90% (95/105) of victims were men with mean age of 17.5 years (74% under 18 years). In all, 40% (32/81) of injuries occurred at home and 53% (43/81) in a public place. 23% (19/84) of injuries were deliberate, 66% (69/104) of injuries were severe and 20% (21/105) resulted in ruptured globes. In all, 54% (48/89) required hospital admission and 41 required surgery. A total of 11% (12/105) of eyes were either enucleated or eviscerated. Final visual acuity was ⩽counting fingers in 29% (26/91) but >6/12 (Snellen) in 65% (59/91). Moderate/significant cosmetic deformities were recorded in 10% (8/77) and restricted ocular movements in 5% (4/72). Conclusions Ocular air gun injuries damage sight and leave lasting morbidity. The demographics and circumstances of injury are well documented with access to, and unsupervised use of, air guns, appearing the principal risks for injury.